Proceedings of the Symposium on Spatial User Interaction 2018
DOI: 10.1145/3267782.3267785
|View full text |Cite
|
Sign up to set email alerts
|

Pocket6

Abstract: We propose, implement and evaluate the use of a smartphone application for real-time six-degrees-of-freedom user input. We show that our app-based approach achieves high accuracy and goes headto-head with expensive externally tracked controllers. The strength of our application is that it is simple to implement and is highly accessible -requiring only an off-the-shelf smartphone, without any external trackers, markers, or wearables. Due to its inside-out tracking and its automatic remapping algorithm, users ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Prior work on target pointing mostly considered linear (e.g., in meters or pixels) target width and amplitude [5,20,24,42,45,51,63,66]. Later, angular measurements (i.e., in degrees or radians) of target width and amplitude were explored for pointing tasks [35][36][37].…”
Section: Target Width Target Amplitude and Idsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work on target pointing mostly considered linear (e.g., in meters or pixels) target width and amplitude [5,20,24,42,45,51,63,66]. Later, angular measurements (i.e., in degrees or radians) of target width and amplitude were explored for pointing tasks [35][36][37].…”
Section: Target Width Target Amplitude and Idsmentioning
confidence: 99%
“…Numerous studies have used Fitts law to explore users' pointing performance on large physical displays [5,24,42,45,51,63,66]. These studies revealed that users' performance is significantly affected by target width and amplitude (i.e., the distance between two targets in meters or pixels).…”
Section: Introductionmentioning
confidence: 99%
“…Using only the smartphone to enable the interaction with a distant display allows users to use their fingers for touch inputs and movement of their device-holding hand for hand motion input. These device-tracking inputs are enabled by the device's touchscreen [5] and pose tracking (i.e., device tilting [1,24] as orientation, motion as translation [3,25], or pose as translation + orientation [2]), while touch-input and tilting the device represent the majority of the past as well as recent papers, we can see a trend towards utilizing SLAM [26] that is natively implemented on modern smartphones, e.g., ARCore [27], ARKit [28]. These libraries show how SLAM can be used for precisely tracking the absolute worldspace pose of the smartphone (i.e., the motion of the user's device-holding hand) in distant display scenarios [2].…”
Section: Tracked Input Modalitiesmentioning
confidence: 99%
“…These device-tracking inputs are enabled by the device's touchscreen [5] and pose tracking (i.e., device tilting [1,24] as orientation, motion as translation [3,25], or pose as translation + orientation [2]), while touch-input and tilting the device represent the majority of the past as well as recent papers, we can see a trend towards utilizing SLAM [26] that is natively implemented on modern smartphones, e.g., ARCore [27], ARKit [28]. These libraries show how SLAM can be used for precisely tracking the absolute worldspace pose of the smartphone (i.e., the motion of the user's device-holding hand) in distant display scenarios [2]. However, approaches that would extend currently known device-tracking inputs for body-tracking of the user's body, head pose as well as gaze still remain undiscovered (see Supplementary Materials).…”
Section: Tracked Input Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation